Legislative Lethargy' in Protecting Informal Women Workers: Understanding the Legal Discourse on 'Paid Domestic Work' in India - Sophy, K.J. (Economic and Political Weekly, 2024)
Despite strong mobilisation efforts since 1953 and numerous private member bills, domestic workers in India remain unrecognised as a sector requiring welfare and protection. This paper examines the legislature's historical approach to DWs, arguing that le
Keywords: Domestic Workers; Informal Women Workers; Legal Discourse; Paid Domestic Work; Legislative Lethargy